PENGARUH INOVASI PRODUK DAN PERSEPSI KUALITAS PRODUK TERHADAP MINAT BELI PADA “CAFÉ TENTANG KOPI” - Ananda, Theresia; Riana, Ausy; Arifin, Anwar (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2024)
The purpose of this study was to determine the buying interest of the café about coffee in Sangatta through the variables of product innovation and perceived product quality. The existence of a café about coffee today is not only a place to spend time while enjoying a cup of coffee, but also as a meeting place to share information about the condition of the surrounding environment and has become a lifestyle for the community. From the results of the analysis of the discussion conducted by the author, the research results show that simultaneously product innovation and perceived product quality have an effect on buying interest in cafes about coffee and partially perceived product quality has a significant effect on buying interest. However, product innovation does not have a significant effect on buying interest in cafes about coffee in Sangatta, while the simultaneous effect of product innovation, perceived product quality has a significant effect on buying interest